Actual and Popularly Attributed Placement of Political Attitudes on the Left-Right Scale: Results from a Representative Survey of Turkey - Alper Yağcı (Siyasal: Journal of Political Sciences)
Individuals’ self-placement on the left-right scale continues to be a staple of voting studies, but the semantic content of this scale is rarely explored. This study aims to examine the discrepancy between the actual and perceived meanings of the political left-right divide among ordinary people, based on original data from a representative sample of Turkey. Are economic issues as pertinent to subjectively held left-right placements as people think? In order to empirically address this question, we develop measures for both parts of the question, i.e. how people endorsing certain economic positions place themselves on the left-right scale, as well as what left-right placement they attribute to a hypothetical person endorsing the same positions. We ask similar questions about non-economic issue positions too, all together comparing six issues. The results show that while the semantic content of the left-right scale in contemporary Turkey is mostly about secularism—a non-economic issue—and is popularly understood as such, it is more about environmentalism, and less about economic issues, than what people think. Endorsement of gender equality and freedom of thought also prove to be substantial correlates of a leftward self-placement and they are popularly recognized as such.